Revolusi Literasi Alam pada Strategi Manajemen Layanan Khusus dengan Pemanfaatan ICT di Sekolah Alam - Diah Anita Ludfiana; Imron Arifin; Agus Timan; Ali Imron (Jurnal Paedagogy, 2023)
This study aims to explore the implementation of the nature literacy revolution, particularly service management strategies using information and communication technology in two Nature Schools, namely SD Anak Saleh and MI Bilingual Al Ikhlas. The research method employed in this study was a qualitative case study approach involving school principals, teachers, nature school coordinators, and students as informants. This research data was obtained through observation, interviews, and literature review techniques, which were then analyzed using an interactive model. The study's findings reveal the significant role of Nature Schools in transforming the educational paradigm, making nature experiences the core of learning, and leveraging ICT to enhance students' ecological understanding. Despite both schools successfully creating inclusive environments and integrating ICT into the learning process, challenges such as financial support and community interest persist. These research findings provide insights into how the Nature Literacy Revolution can be realized through Nature Schools and inspire other educational institutions to adopt a similar approach—emphasizing nature experiences, collaborative learning, and experience-based approaches.